Trudie Styler's strengthen & restore yoga [videorecording (DVD)]. - Styler, Trudie; D'Silva, James (Living Arts/Gaiam, 2011)
Trudie Styler and renowned yoga instructor James D'Silva bring four unique practices designed to strengthen the body while calming the mind, creating the ultimate balance in life. Discover the powerful combination of burning calories and toning muscle while learning to focus and relax. Programs include: Trudie's Toning Practice, Strong Body & Mind, Breathe Easy, and Calming Meditation.